2002
DOI: 10.1007/bf02723698
|View full text |Cite
|
Sign up to set email alerts
|

Child with a tail

Abstract: An interesting case of a child with a tail is reported. The child had a tail like structure in the back since birth, increasing with age. It was 20 cm. long, the longest tail so far described in the English literature. There was no functional complain. The result was excellent after excision as the problem was only cosmetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…With one exception, all other cases reported with MR or CT myelography imaging have described a direct extension of the tail mass through the fascia and dura into the spinal cord, similar to a lipomyelomeningocele or dermal sinus tract [3, 4, 8, 9, 12, 13]. There have been several other cases published prior to the availability of MR where the authors reported no subfascial extension of the tail [5, 6, 10, 14], but only one other case has been reported with MR imaging, in 1988 by Dubrow et al [2]. In that case there was no spinal lipoma or tethered cord at all.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With one exception, all other cases reported with MR or CT myelography imaging have described a direct extension of the tail mass through the fascia and dura into the spinal cord, similar to a lipomyelomeningocele or dermal sinus tract [3, 4, 8, 9, 12, 13]. There have been several other cases published prior to the availability of MR where the authors reported no subfascial extension of the tail [5, 6, 10, 14], but only one other case has been reported with MR imaging, in 1988 by Dubrow et al [2]. In that case there was no spinal lipoma or tethered cord at all.…”
Section: Discussionmentioning
confidence: 98%
“…Human tails have been reported of various lengths (range 1–20 cm) and at various levels of the spine from the lower coccyx to the upper lumbar region [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. They may be in the midline or off to one side, and rarely is there a history of family members born with a tail.…”
Section: Discussionmentioning
confidence: 99%
“…These tails had additional vertebrae and were connected to the tip of the coccyx. The authors reasoned that these structures should be categorized as true human tails because they arose due to non-regression of the embryonic tail (Sugamata et al, 1988;Islam, 2002). Keita et al (2006) described three cases of tails containing vertebrae and classified them all as true human tails.…”
Section: Classification Of Tailsmentioning
confidence: 99%
“…Spina bifida of S1 was the only abnormality of the sacrum noted (Bar-Maor et al, 1980). These cases involved patients with the normal number of vertebrae, but another report by Sugamata et al (1988) involved two cases of tails with additional vertebrae (Islam, 2002). Since the classification criteria involve non-regression of the embryological tail, these should still be termed true tails (Dao and Netsky, 1984;Sugamata et al, 1988;Islam, 2002;Cai et al, 2011).…”
Section: Illustrative Cases Of True Tailsmentioning
confidence: 99%
See 1 more Smart Citation